Development and validation of a novel UPLC-Q-Orbitrap HRMS method for determining p-Nitroaniline and its metabolites in blood - Wang, Peng; Wang, Junlin; Xu, Qiuliang; Zou, Hua; Gao, Xiangjing; Ren, Hong; Cao, Yiyao (Frontiers in Chemistry, 2025)
An accurate, reliable, and sensitive method was successfully developed to simultaneously determine p-Nitroaniline (p-NA) and its metabolites in blood based on the hyphenated technology of quadrupole-orbitrap high resolution mass spectrometry (Q-Orbitrap HRMS) and ultra-performance liquid chromatography (UPLC). After the blood sample was extracted with ethyl acetate, the organic layer was taken for injection and analysis. Within the concentration range of 1–100 μg/L, the calibration curves of p-NA and its metabolites had a good linearity, with correlation coefficient(r) values greater than 0.999. This method has excellent precision and accuracy. The intra- and inter-day coefficients of variation (CVs) were less than 9.9% and 8.7% respectively, and the analytical accuracy ranged from 83.1% to 101.3%. The lower limits of detection (LLODs) for all target analytes were between 0.6 μg/L and 2.2 μg/L, and the lower limits of quantification (LLOQs) were between 2.0 μg/L and 7.4 μg/L. In addition, the application potential of this method was verified by analyzing the blood samples of workers exposed to p-NA. The results indicated that this method was accurate, reliable and sensitive, and was applicable to the detection of p-NA and its metabolites in the blood.